2014
DOI: 10.3389/fevo.2014.00058
|View full text |Cite
|
Sign up to set email alerts
|

Learned predation risk management by spider mites

Abstract: Predation is a prime selective force shaping prey behavior. Investment in anti-predator behavior is traded-off against time and energy for other fitness-enhancing activities such as foraging or reproduction. To optimize this benefit/cost trade-off, prey should be able to innately and/or by experience modulate their behavior to the level of predation risk. Here, we assessed learned predation risk management in the herbivorous two-spotted spider mite Tetranychus urticae. We exposed spider mites coming from benig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 33 publications
2
14
0
Order By: Relevance
“…Moreover, Hirayama and Kasuya () found that predator‐experienced water striders oviposit at deeper positions underwater not to avoid current risks, but rather, to avoid future egg parasitism (i.e., precautionary antipredator behavior). Our findings confirmed spider mites’ potential for adaptive learning (e.g., Agrawal, Vala & Sabelis, ; Egas & Sabelis, ; Hackl & Schausberger, ), and suggest that the potential influences of predators on parental care for offspring in many other organisms may have been underestimated and require further study.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Moreover, Hirayama and Kasuya () found that predator‐experienced water striders oviposit at deeper positions underwater not to avoid current risks, but rather, to avoid future egg parasitism (i.e., precautionary antipredator behavior). Our findings confirmed spider mites’ potential for adaptive learning (e.g., Agrawal, Vala & Sabelis, ; Egas & Sabelis, ; Hackl & Schausberger, ), and suggest that the potential influences of predators on parental care for offspring in many other organisms may have been underestimated and require further study.…”
Section: Discussionsupporting
confidence: 83%
“…Censored Experienced Naïve behavior). Our findings confirmed spider mites' potential for adaptive learning (e.g., Agrawal, Vala & Sabelis, 2002;Egas & Sabelis, 2001;Hackl & Schausberger, 2014), and suggest that the potential influences of predators on parental care for offspring in many other organisms may have been underestimated and require further study.…”
Section: (C)supporting
confidence: 75%
“…They avoided overreaction and saved energy by being less restless in presence of predator traces alone. We argue that the observed behavioral changes represent optimized risk management, as has been shown for various animals including fish, salamanders and spider mites 26 27 28 , i.e. an attenuated response to alarm and/or predator traces following physical predator experience.…”
Section: Discussionmentioning
confidence: 54%
“…During the learning phase, larvae and early protonymphs were exposed to high IGP risk (physical presence of predator females, their eggs and traces) whereas, in the choice situation, late protonymphs were exposed to sites with and without predator traces, indicating latent risk. Since the predator-experienced protonymphs acted bolder towards predator traces than the naïve ones did, our experiment suggests that learning allowed the protonymphs to distinguish between immediate and latent IGP risks 1 7 8 26 . Since every anti-predator behavior has costs, misjudging the risks associated with a given predator or cue would have negative consequences for prey.…”
Section: Discussionmentioning
confidence: 84%
“…they respond less actively to predators. For example, predator-experienced spider mites attenuated their anti-predator responses to predator cues [ 5 ].…”
Section: Introductionmentioning
confidence: 99%